Mae Jemison - Shepherd, Jodie (New York : Children's Press, 2015)
Looks at the life of Mae Jemison, the first African-American astronaut.
Includes index.
3.5
K-3
790L
Keywords: Jemison, Mae, -- 1956- -- Juvenile literature; Women astronauts -- Biography -- Juvenile literature; Astronauts -- United States -- Biography -- Juvenile literature; Jemison, Mae, -- 1956-; Astronauts; African Americans -- Biography; Women -- Biography; Biographies